Suscetibilidade diferenciada de Synedrellopsis grisebachii ao herbicida glyphosate: efeito do sombreamento e do estágio de desenvolvimento - Santos, Juciléia Irian dos [UNESP] (2015)
Susceptibility to herbicides is related to several factors, including the environmental conditions in which these plants are developed. According this information two experiments were carried out (vegetative and full bloom stages of plant development) and the aim was to correlate the tolerance of Synedrellopsis grisebachii to glyphosate and their leaf anatomy, by distinct light intensities. The treatments were arranged in 2 x 7 factorial design, consisting of two light intensity (sun and shade) and seven glyphosate rates (0; 450; 900; 1,800; 3,600; 7,200 e 10,800 g e. a. ha-1). The herbicide application was performed when the plants were in the stages of development proposed at work. Analysis of leaves anatomy was performed at 0 and 7 days after the application (DAA). The metabolic compounds ware quantified also at 7 DAA, by LC-MS/MS system and the visual control was evaluated at 14, 21, 28 and 35 DAA. The sunlight changed the leaf anatomy of S. grisebachii who acted as barriers absorption of glyphosate giving greater tolerance in a high light intensity (sun). The herbicide action was more effective in plants under low light intensity (shadow), leading to greater absorption of herbicide, greater injury in the leaves, greater accumulation of shikimic acid and faster control and in smaller rates, than plants under high light intensity. Plants in full bloom stage are less susceptible to the action of glyphosate than in vegetative stage of plant development